Social media: What impact on the reputation and e-reputation of SMEs in the Souss Massa region - KANANE , Badereddine; SKOURI , Hassan; ADERDOUR , Meryam (Revue Internationale du Chercheur, 2023)
This exploratory study is part of the perspective of shedding light on the use of social media by SMEs in the Souss Massa region and the impact of these media on their reputation. To this end, we conducted a study with a limited sample of SMEs in the region through semi-directive interviews with 22 managers of these companies. The results obtained showed that social media have a positive impact on the reputation and notoriety of the companies that were the subject of the research. A number of contributions, limitations and research perspectives are discussed.